Are the Effects of Legitimacy and Its Components Invariant? Operationalization and the Generality of Sunshine and Tyler's Empowerment Hypothesis. (February 2021) - Fox, Bryanna; Moule, Richard K.; Jaynes, Chae M.; Parry, Megan M.
Objectives: To assess whether the relationship between legitimacy and police empowerment is sensitive to the operationalization of legitimacy, and whether the effects of legitimacy and its components on empowerment are invariant. Empowerment is examined in the context of police militarization—public support for the discretionary use of surplus military equipment by law enforcement. Method: Using a national sample of 702 American adults and a series of ordinary least squares regressions, the direct and interactive effects of legitimacy and its components on empowerment are examined. Results: The composite measure of legitimacy, as well as its individual components, each exert direct effects on police empowerment. Instrumental factors have persisting, albeit weaker, effects relative to normative factors. Interaction terms between the composite legitimacy measure or its components and sociodemographic characteristics were not statistically significant. In short, the effects of legitimacy and its components on empowerment appear invariant. Conclusions: Findings provide additional evidence of the generality of Tyler's process–based model and extend these considerations to the burgeoning literature on public empowerment of police.